Clinical spectrum of systemic lupus erythematosus in children. Case report. - Reyes-Florián, Giuliana (2021)
Systemic lupus erythematosus is an autoimmune disease with multisystem involvement, an alternating clinical course, and which constitutes a diagnostic challenge, with a greater disease activity in the pediatric age group, which also darkens its prognosis. In this article, we report the case of a ten year old female patient who debuted with systemic lupus erythematosus with gastrointestinal, renal and hematological involvement; the chronic course coupled with the varied clinical spectrum suggested the diagnostic possibility.